AN ANALYSIS OF ENGLISH TEACHERS’ STRATEGIES IN TEACHING WRITING SKILL AT SENIOR HIGH SCHOOL 1 MAJENE - Albar, Ade Fitriah; Nurdin Noni; Iskandar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This thesis aims to find out the teacher’s strategy in teaching writing skill in the class of the second-grade students at SMA Negeri 1 Majene, to find out the problem faced by teachers in teaching writing skill of the second-grade students at SMA Negeri 1 Majene, and to find out how the teachers implement strategy in teaching writing skill of the second-grade students at SMA Negeri 1 Majene. This research was conducted at Senior High School 1 Majene, the subjects of this research are two English teachers who taught the second-grade students. This research used qualitative research. This research used an observation checklist and interviews to collect the data. the researcher used three steps to analyze the data, there are data condensation, data display, and drawing and verifying conclusion. The findings revealed that both teachers employed the Project-Based Learning (PBL) strategy for teaching writing. The first teacher also used video-based learning and the second teacher also used mind mapping strategy However, In terms of implementation, there were both similarities and differences in the teachers' approaches. Both teachers used collaborative learning by group assignments and encouraged presentations for assessment. However, the first teacher used various learning media like projectors, speakers, and visual aids to enhance understanding, while the second teacher primarily relied on textbooks. They encountered several challenges, such as diverse student characteristics, some students' preference for studying outside the classroom, the need for visual examples during group work, and issues with student participation and timely submission of assignments